Effect of the Organobentonite Filler on Structure and Properties of Composites Based on Hydroxyethyl Cellulose. (14th September 2017) - Alekseeva, Olga V.; Rodionova, Anna N.; Bagrovskaya, Nadezhda A.; Agafonov, Alexander V.; Noskov, Andrew V.
Abstract : Organobentonite powder was synthesized and characterized using laser diffraction, X-ray diffraction, low-temperature nitrogen adsorption-desorption technique, and dynamic light scattering. Obtained powder was found as material with mesopores. The organobentonite particles were larger than pure bentonite one. Hydroxyethyl cellulose (HEC) was filled with organobentonite particles by mechanical dispersion, and produced composite films were researched by the number of methods. New data relating to structure, tensile properties, and antimicrobial activity of HEC/organobentonite composites were obtained. Using results of X-ray diffraction, the reflections assigned to crystal filler in polymer material were proved. Concentration effect of the filling agent on tensile properties of composite film was revealed. Data of infrared (IR) spectrometry indicated a decrease in the density of hydrogen-bond net in HEC/organobentonite composite as compared with pristine HEC. Using microbiological tests, it was found that the HEC/organobentonite films exhibited bacteriostatic action against S. aureus and fungistatic action against molds.